Analisis Pesan Moral Pada Film The Covenant Karya Guy Ritchie’s - Ferizon, Jordi; Putra, Dilmai; Sari, Sapta (Jurnal Multidisiplin Dehasen (MUDE), 2025)
A good film should not only function as a medium of entertainment, but also educate its audience and contain various important information about the plot of the film. The film "The Covenant" is an American action drama film directed by Guy Ritchie's. This study aims to describe the meaning of the moral message contained in the film. "The Covenant. This study is a qualitative descriptive study using Roland Barthes' semiotic analysis approach. Data collection in this study used observation and documentation. The results of the study show that the moral messages contained in the film "The Covenant" are: 1) Doing work that is considered a traitor for the sake of the family is the importance of sacrifice and priority to always pay attention to those closest to us. 2) Failure, failure can occur due to unexpected factors, and it reminds us to remain humble, failure can also be a valuable teacher. 3) Repaying the kindness of those who have saved our lives Repaying kindness is not only about physical actions, but also about showing gratitude and appreciating the sacrifices of others. 4) Teaches about fortitude, patience, and acceptance of the reality of life that does not always go according to expectations. The meaning of denotation, connotation and myth conveyed by the director and writer make the film "The Covenant" worth watching because it is thick with moral messages that are full of struggle and gratitude. .